A New DNA Repair-Related Platform for Pharmaceutical Outlook in Cancer Therapies: Ultrashort Single-Stranded Polynucleotides - Sergey Stovbun; Kirill Ermakov; Alexander Bukhvostov; Alexander Vedenkin; Dmitry Kuznetsov (MDPI AG, 2019)
Thio- and cyano- modified single-stranded poly(dNTP) sequences of different molecular sizes (20−200 n) and the same lengths routine poly(dNTP) and poly(NTP) species were tested for their impact on catalytic activities of β-like DNA polymerases from chromatin of HL-60, WERI-1A and Y-79 cells as well as for the affinity patterns in DNApolβ-poly(dNTP)/(NTP) pairs, respectively. An essential link between the lengths of ultrashort (50−100 n) single-stranded poly(dNTP) sequences of different structures and their inhibitory effects towards the cancer-specific DNA polymerases β was found. A possible significance of this phenomenon for both DNA repair suppression in tumors and a consequent anti-cancer activity of the DNA repair related short poly(dNTP) fragments is under discussion.